Розроблення крафтового напою для вегетаріанців - Дударєв, Ігор Миколайович; Dudarev, Igor; Ющук, Сергій; Yushchuk, Serhiy; Кухар, Ростислав Юрійович; Kukhar, Rostyslav (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: Унаслідок збільшення у світі кількості прихильників здорового харчування та вегетаріанства потребує розширення асортимент безалкогольних напоїв з рослинної сировини. Тому мета дослідження – розробити крафтовий напій для вегетаріанців та дослідити його фізико-хімічні й органолептичні властивос-ті. Розроблений крафтовий напій містить рецептурні компоненти: напій вівсяний, сік яблучний і чай чорний. Напій має високі органолептичні властивості, зокрема, приємний яблучний смак та запах. Густина напою – 1031 ± 2,8 кг/м3, уміст сухих речовин – 7,80 ± 0,15 % та активна кислотність (рН) 4,6. Калорійність напою 39,1 ккал/100 г, а його поживна цінність (мас. %): білки 0,62; жири 1,25; вуглеводи 6,34. Напій може бути рекомендований до впровадження на крафтових виробництвах безалкогольних напоїв та в закладах ресто-ранного господарства. /// EN: Due to the increasing number of supporters of healthy eating and vegetarianism worldwide, there is a need to expand the range of soft drinks made from plant-based ingredients. Vegetarian consumers are often concerned about the ingredients in their food and drink and are looking for options that meet their values and dietary preferences. Craft soft drinks made with natural, plant-based ingredients can offer a unique, flavourful experience that meets the needs of this conscious consumer group. Therefore, the aim of this study was to develop a craft soft drink for vegetarians and study its physicochemical and sensory properties. Five craft drink samples were developed, containing different proportions of oat drink, apple juice, and black tea. The physicochemical properties of the samples were determined using standard methods. The sensory properties of the samples were evaluated using an expert method. The nutritional value and caloric content of the samples were calculated. The best sample, based on sensory properties, was a drink containing 50 % oat milk, 30 % apple juice, and 20 % black tea. This soft drink had high sensory properties, including a pleasant apple taste and smell. It had a homogeneous liquid consistency and a light yellow-beige colour. Taking into account the weighting coefficients determined for the sensory properties, the complex quality index of the soft drink was calculated to be 0.917. The density of the soft drink was 1031 ± 2.8 kg/m³, the dry matter content was 7.80 ± 0.15 %, and the active acidity (pH) was 4.6. The caloric content of the developed soft drink was 39.1 kcal/100 g, and its nutritional value was as follows (wt. %): proteins 0.62, fat 1.25, and carbohydrates 6.34. The soft drink contains no added sugar and is enriched with nutrients derived from its plant-based ingredients. The developed craft soft drink can be recommended for production in the craft industry and for use in restaurants.
Development of a craft drink for vegetarians
Keywords: безалкогольний напій; вівсяне молоко; сік яблучний; чай чорний; вегетаріанський напій; густина напою; soft drink; oat milk; apple juice; black tea; vegetarian drink; drink density